Decolonizing Qurʾanic Studies - Joseph Lumbard (19488229) (2022)
The legacy of colonialism continues to influence the analysis of the Qurʾan in the Euro-American academy. While Muslim lands are no longer directly colonized, intellectual colonialism continues to prevail in the privileging of Eurocentric systems of knowledge production to the detriment and even exclusion of modes of analysis that developed in the Islamic world for over a thousand years. This form of intellectual hegemony often results in a multifaceted epistemological reductionism that denies efficacy to the analytical tools developed by the classical Islamic tradition. The presumed intellectual superiority of Euro-American analytical modes has become a constitutive and persistent feature of Qurʾanic Studies, influencing all aspects of the field. Its persistence prevents some scholars from encountering, let alone employing, the analytical tools of the classical Islamic tradition and presents obstacles to a broader discourse in the international community of Qurʾanic Studies scholars. Acknowledging the obstacles to which the coloniality of knowledge has given rise in Qurʾanic Studies can help us to develop more inclusive approaches in which multiple modes of analysis are incorporated and scholars from variegated intellectual backgrounds can engage in a more effective dialogue. Other Information Published in: Religions License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/rel13020176